Clinically reliable cognitive decline in relapsing remitting multiple sclerosis: Is it the tip of the iceberg?. (2nd July 2020) - Andravizou, Athina; Siokas, Vasileios; Artemiadis, Artemios; Bakirtzis, Christos; Aloizou, Athina-Maria; Grigoriadis, Nikolaos; Kosmidis, Mary H.; Nasios, Grigorios; Messinis, Lambros; Hadjigeorgiou, Georgios; Dardiotis, Efthimios; Peristeri, Eleni
ABSTRACT: Objectives: Cognitive impairment is common in multiple sclerosis, but the brain MRI correlates in relapsing remitting multiple sclerosis remain controversial. The current study aimed to investigate whether cognitive decline can be predicted by global and/or regional brain atrophy. Methods: Sixty-three patients with relapsing remitting multiple sclerosis (36 men, mean age 39.9 ± 9.4 years old, mean EDSS 1.4 ± 1.2, mean disease duration 4.9 ± 4.3 years) and 46 healthy controls (21 men, mean age 37.5 ± 10.8 years old) were included. Demographic data were obtained, and a longitudinal neuropsychological and global and regional MRI brain volume assessment was performed. Results: The patients performed worse than controls in most neuropsychological tests at baseline. The percentage of patients with clinically meaningful cognitive decline ranged from only 0% to 7.9%. Statistically significant volume reduction was found for all MRI measures except for the left accumbens nucleus. Whole or regional brain atrophy ranged from −0.02% to −0.25%, with subcortical structures showing the largest atrophy rates. A total of 22.2% to 93.7% patients showed atrophy across the brain structures assessed volumetrically. Discussion: It was regional rather than whole-brain changes that significantly predicted cognitive decline for the patients in the tasks that tested processing speed, visuo-spatial and inhibition skills. The overall data suggest that the progression of cognitive impairment in relapsing remitting multiple sclerosis as captured by conventional neuropsychological testing is the tip of the iceberg of neurodegenerative sequelae in the disease. Also, regional volumetric changes are better than whole-brain atrophy at predicting cognitive dysfunction.